Integrating Climate Change into English Language Teaching: A Survey of Indonesian Teachers' Preparedness and Perspectives. - Silvhiany, Sary; Rahmadhani, Sakilah; Inderawati, Rita; Meilinda, Meilinda; Trilestari, Kuntum (VELES Voices of English Language Education Society, 2023)
Climate change is one of the most critical issues we are currently facing. Considering the devastating impact of climate change to many people in the world, an interdisciplinary approach to climate change mitigation is highly essential. Teachers have a crucial responsibility in transferring knowledge, persuading students, and setting an example for critical thinking and environmental advocacy in order to prepare students for the challenges posed by climate change. The issue of climate change is one of the topics and goals of EFL teachers in preparing students to face climate change. The aim of this research is to explore teachers' knowledge, beliefs, attitudes and preparedness in integrating climate change issues in ELT. This study employed a survey method, which involved 214 Indonesian EFL teachers from various levels of education, from elementary to high school. Data were analyzed through questionnaires, consisting of four parts: teachers’ knowledge, belief, attitude and preparedness in integrating climate change issues in ELT. The results show that there is a correlation between knowledge, belief and attitude towards preparedness in incorporating climate change education in EFL learning. Moreover, most teachers expressed their willingness to teach climate change issues in ELT, despite the score of their knowledge, belief, and attitude regarding climate change. These results shed light on teachers’ understanding of climate change, belief about, and attitude toward climate change issues. Implications of the study include the possibility of incorporating climate change education in EFL learning and EFL sustainable teacher education.